The influence of entrepreneurial orientation and financial performance on sustainable business in MSMEs - Satria, Gde Agung; Wiagustini, Ni Luh Putu; Rahyuda, Henny; Candraningrat, Ica Rika (Indonesian Journal of Multidisciplinary Science, 2023)
The research examines the influence of Enterpreneuship orientation and financial perfrmance on sustainable businesses in micro, small and medium enterprises that are challenges in influencing the economy. This qualitative research study utilized a systematic literature review on scientific journals from 2015-2023, focusing on entrepreneurial orientation, financial performance, and sustainable business, and analyzed through data reduction, presentation, and conclusions. The results of this study show that the Entrepreneurship orientation has an influence on the financial performance of new product development. This, to improve tha performance of new product development, current and future customer needs should be seen as a guideline for new product development efforts. Where, the Entrepreneurship orientation that affects the influence on the performance of micro small and medium enterprises is only an autonomous dimension. While other dimensions of enterpreneurship orientation such as innovation, proactive and risk odo not have a significant effect on the performance of micro, small and medium enterprises. Therefore, it is recommended to provide autonomy to employees to be able to motivate them by giving freedom to act in an entrepreneurship manner so that they can improve the performance of micro, small and medium enterprises.